Soluble receptor for advanced glycation end products in patients with decreased renal function - Kalousová, Marta; Hodková, Magdaléna; Kazderová, Markéta; Fialová, Jana; Tesar, Vladimír; Dusilová-Sulková, Sylvie; Zima, Tomás (American journal of kidney diseases, 2006)
BACKGROUND: Advanced glycation end products (AGEs) accumulate in patients with decreased renal function and exert various toxic effects through the receptor for AGEs (RAGE). Soluble RAGE (sRAGE) is a naturally occurring inhibitor of AGE-RAGE action. The aim of the study is to describe the relationship of sRAGE to renal function and dialysis modalities. METHODS: The studied group consisted of 81 patients: 25 patients with various degrees of decreased renal function, 20 long-term hemodialysis (HD) patients, 15 peritoneal dialysis (PD) patients, and 21 healthy age-matched subjects. sRAGE was assessed immunochemically (enzyme-linked immunosorbent assay), and routine biochemical parameters were measured by means of certified methods. RESULTS: sRAGE level correlates positively with serum creatinine concentration (r = 0.50; P < 0.05), and its relationship to creatinine clearance is hyperbolic. sRAGE levels are elevated significantly, mainly in patients with end-stage renal disease (3,119.0 +/- 968.4 pg/mL in HD patients and 3,652.7 +/- 1,677.7 pg/mL in PD patients versus 1,405.1 +/- 426.1 pg/mL in controls; both P < 0.001 versus controls). In PD patients, sRAGE is detectable in spent dialysate (median, 75.8 pg/mL), correlates with its serum levels (r = 0.67; P < 0.05), and is related to protein losses in dialysate. In HD patients, sRAGE levels increase by 50% (P < 0.001) from 0 to 15 minutes during both HD and hemodiafiltration, and then decrease until the end of the session. CONCLUSION: Serum sRAGE levels increase in patients with decreased renal function, mainly patients with end-stage renal disease. It remains to be elucidated whether the increase is caused just by decreased renal function or whether sRAGE is upregulated to protect against toxic effects of AGEs.
Keywords: Renal Dialysis; receptory imunologické; ledviny; Kidney Failure, Chronic; Female; Receptor for Advanced Glycation End Products; Receptors, Immunologic; Kidney; Humans; ženské pohlaví; chronické selhání ledvin; mužské pohlaví; dialýza ledvin; lidé; Male; lidé středního věku; Middle Aged; receptor pro konečné produkty pokročilé glykace